(untitled) (Journal of Plant Disease Sciences, 2022)
Acid lime seed and seedling are susceptible to both biotic and abiotic stresses, which cause poor germination and pre- and post-emergence damping off. Damping off caused by Fusarium solani and Rhizoctonia bataticola is probably the worst enemy to acid lime seedlings plants in nursery. To find out the effectiveness of six chemical fungicides, poison food technique was used against F. solani and R. bataticola and results revealed that fungicides carboxin 37.5% + thiram 37.5% DS, metalaxyl 8 % + mancozeb 64% WP and carbendazim 12 % + mancozeb 63 % WP were found to be the most effective as completely inhibiting the growth of tested pathogens. Among the microbial antagonists, Trichoderma harzianum was found to be more promising than Pseudomonas fluorescens and Bacillus subtilis in inhibiting pathogens growth.